Kinerja Lingkungan, Corporate Social Responsibility (CSR) dan Profitabilitas Perusahaan Pertambangan - Neks Triani; Sabarudin; sasmita Nabila Syahrir; Elpa Parinding; Riad Afrillah (Politeknik Ganesha Medan, 2025)
This study aims to ascertain how mining industry profitability is impacted by corporate social responsibility and environmental performance. This quantitative study looks at how mining companies' profitability is affected by corporate social responsibility (CSR) and environmental performance (PROPER). The study's sample consisted of Indonesian public mining businesses that were listed between 2020 and 2023 on the Indonesia Stock Exchange. Eleven businesses in the mining industry served as the study's samples. Regression with fixed, random, and common effect models were used to analyze the study. The study's findings showed no correlation between profitability and environmental performance (PROPER), indicating that the Ministry of Environment's environmental performance standards have no effect on profitability.